Health professionals exposed to tuberculosis: an integrative review (Research, Society and Development, 2020)
Tuberculosis is configured as an infectious disease worldwide known, however, there are still many challenges to be overcome regarding its occurrence even today. The objective was to know the scientific production about the exposure of health professionals to tuberculosis. It is an integrative literature review, which used the databases: MEDLINE, LILACS and BDENF, three delimiters were used: main descriptor: tuberculosis; secondary descriptors: exposure and health professionals; publication period from 2000 to 2017 in Portuguese and English. The bibliographic survey, for the integrative review, took place between the months of September and October of the year 2018, using the thematic analysis technique, emerging five categories: personal protective equipment and tuberculosis; need for isolation and tuberculosis; appropriate environments for patients with suspected / confirmed tuberculosis; hospital management and tuberculosis control; knowledge of health professionals and tuberculosis control. It was concluded that there are deficiencies in the control and safety of health professionals in the face of tuberculosis, therefore it is essential the action of the managers of the institutions and the clarification of health professionals regarding the risk to which they are exposed.